O ensino superior na sociedade da informação e do conhecimento na ótica da UNESCO e do Banco Mundial - Fernandes, José Eduardo (2015)
This thesis is attached to the research 1 – Educational Institution: Organization and Management, from the Master’s Program in Education of the Oeste Paulista University (UNOESTE – Presidente Prudente – SP), and analised that the society is situated in a paradigm which the information spreads quickly and this is happening due to the fact of the using of range of technologies which allows the available as well as this information exchanged through spread people all over the world. Thus this technologies allow people who are connected through a extended network which, paradoxically, keep them so close and so distant at the same time, characterized virtual interaction spaces. This analysis came from official documents from UNESCO and Banco Mundial in comparison of guidelines designed by this institutions to the countries in development which includes Brazil. Factors like globalization, opening and expanding transnational economies are also determinants in this new information paradigm as well as in educational process through the consequences of this transnationality of the information and knowledge; their impacts and perspectives from the results gotten with the existent educational politics. Thus its objective concentrated in understand the Higher Education, its demands and perspectives within called “Information and Knowledge” Society in the globalization context, in UNESCO and Banco Mundial perspective as well as Brazil’s position in front of these two proposes. Within this context the option made was work with the bibliographic research and documentation to reflect about Higher Education, its demands and perpectives within called “Information and Knowledge” Society.